Neuroblastoma metastasized to the mandible and the spinal extradural regions: A case report - Sun, Xiaomei; Xu, Hui; Xin, Kai; Sun, Bo (Medicine (Baltimore), 2021)
Neuroblastoma (NB) metastasized into the mandible and spinal extradural region was rarely reported. We present a case with metastatic NB to the mandible and the spinal extradural regions. The patient received chemotherapy using NB 97 regimen and was tumor free after 8 months, but 9 months after the treatment, the patient presented with lower limb paralysis and persistent pain in maxillofacial region as well as swelling in the left mandibular area. Metastasis to the mandible and the spinal extradural regions was diagnosed based on the spinal and maxillofacial magnetic resonance imaging. Radiotherapy with a density of 2 Gy per day was given via a linear accelerator. The total dose of the intraspinal occupying lesion was subject to radiotherapy with a regimen of 30 Gy (10 fractions). For the management of the maxillofacial pain, tumor in the maxillofacial region was subject to a density of 50 Gy (25 fractions). The maxillofacial pain disappeared after a density of 10 Gy and soft tissue tumefaction was eliminated after a density of 50 Gy, and the maxillofacial appearance was much better than before. Finally, the patient died from tumor progression 2 years after diagnosis for NB.